Is Sino–American Scientific Collaboration a Thing of the Past? - Zweig, David (International Higher Education, 2021)
A laudatory component of Sino–US rapprochement after 1978 has been collaborative research. But China’s aggressive effort to benefit from its scientific diaspora, the cutting-edge technology that has gravitated to China from the United States, and America’s new perception of China as a “strategic competitor,” led the Trump administration to roll out the “China Initiative,” securitizing scientific collaboration. Despite a strong pushback from universities and Asian–American rights groups, this scientific cooperation remains at risk.